Penggunaan Diksi dan Konjungsi dalam Teks Prosedur Karya Siswa Kelas XI SMA Negeri 1 V Koto Kampung dalam Kabupaten Padang Pariaman - Marzulianis, Marzulianis; Amir, Amril (Al-DYAS, 2023)
The objective of this research is to describe the use of diction and conjunctions in procedural texts written by students of class XI at SMA Negeri 1 V Koto Kampung Dalam, Padang Pariaman Regency. This research is qualitative in nature, using a descriptive method. The data for this research consists of qualitative data in the form of diction and conjunctions used by the students in procedural texts. The data source for this research is the procedural texts written by students of class XI at SMA Negeri 1 V Koto Kampung Dalam, Padang Pariaman Regency. The researcher is the instrument for this research. The data collection technique used is documentation. The data validation technique used in this research is triangulation. From the 29 research data, a total of 3,002 instances of diction were found, consisting of 2,753 instances of accurate diction usage and 249 instances of inaccurate diction usage. The procedural texts written by students of class XI at SMA Negeri 1 V Koto Kampung Dalam, Padang Pariaman Regency tend to be constructed with structured diction, indicating that the students have a good command of appropriate diction. Secondly, the research found a total of 423 instances of conjunctions from the 29 data, consisting of 363 instances of accurate conjunction usage and 60 instances of inaccurate conjunction usage. The procedural texts written by students of class XI at SMA Negeri 1 V Koto Kampung Dalam, Padang Pariaman Regency tend to be constructed with structured conjunctions, indicating that the students have a good command of appropriate conjunctions, especially in their writing. Therefore, students of class XI at SMA Negeri 1 V Koto Kampung Dalam, Padang Pariaman Regency tend to use standard diction and conjunctions that are not yet accurate in writing procedural texts.